Soluble expression of a novel feruloyl esterase from Burkholderia pyrrocinia B1213 in Escherichia coli and optimization of production conditions. Issue 1 (1st January 2020) - Fu, Zhilei; Fan, Guangsen; Zhu, Yuting; Teng, Chao; Li, Hehe; Liu, Qian; Yang, Ran; Li, Xiuting
Abstract: This report examines the soluble expression of a novel feruloyl esterase, BpFae, from Burkholderia pyrrocinia in Escherichia coli overexpression systems using three expression vectors, pET28a, pCold-TF and pGEX-4T-1. BpFae was overexpressed as insoluble inclusion bodies when pET28a was used as the expression vector. BpFae was overexpressed in the soluble form when using pCold-TF; however, the overexpressed protein showed negligible activity. Recombinant BpFae was produced in the soluble form and active when E. coli cells were transformed with the pGEX-4T-1-BpFae vector. Optimal conditions for soluble overexpression of recombinant BpFae were determined, and the highest activity of recombinant BpFae was 2.54 U mL −1 . Multiple sequence alignment, phylogenetic analysis and construction of a three-dimensional model indicated that BpFae is a unique FAE from B. pyrrocinia with underlying research value.